(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
This study aimed to identify the role of digital transformation in improving the quality of the internal audit process. The researchers used the descriptive analytical approach, and the questionnaire was relied on as a study tool that was applied to the study population consisting of internal auditors working in banks listed on the Palestine Stock Exchange, and their number was (85). A checker and a comprehensive inventory method was used due to the small size of the community, where the response data of the questionnaire was analyzed and interpreted using the Statistical Packages Program (SPSS). The results of the study showed that the use of digital transformation contributes to ensuring the quality of the work of the internal auditor and the ability to use electronic data to facilitate the completion and implementation of the audit process with high accuracy. The study recommended that the banks listed on the Palestine Stock Exchange should work on using digital transformation because of its benefit in bringing about fundamental changes in the organization and planning of the audit process and assessing the risks that may face the internal audit process.